Futures of the Contemporary: Contemporaneity, Untimeliness, and Artistic Research - Assis, Paulo de; Schwab, Michael (Leuven Leuven University Press, 2019)
Futures of the Contemporary explores different notions and manifestations of "the contemporary" in music, visual arts, art theory, and philosophy. In particular, the authors in this collection of essays scrutinise the role of artistic research in critical and creative expressions of contemporaneity. When distinguished from "the contemporaneous" of a given historical time, "the contemporary" becomes a crucial concept, promoting or excluding objects and practices according to their ability to diagnose previously unnoticed aspects of the present. In this sense, the contemporary gains a critical function, involving particular modes of relating to history and one's own time.Written by major experts from fields such as music performance, composition, art theory, visual arts, art history, critical studies, and philosophy, this book offers challenging perspectives on contemporary art practices, the temporality of artistic works and phenomena, and new modes of problematising the production of art and its public apprehension.Contributors: Andrew Prior (University of Plymouth), Babette Babich (Fordham University), Geoff Cox (Fine Art at Plymouth University / Aarhus University), Heiner Goebbels (Justus Liebig University), Jacob Lund (Aarhus University), Michael Schwab (Orpheus Institute), Pal Capdevila (Autonomous University of Barcelona), Paulo de Assis (Orpheus Institute), Peter Osborne (Kingston University London), Ryan Nolan (University of Plymouth), Zsuzsa Baross (Trent University)
Keywords: MusicExperimentX: Transdisciplinary Encounters in and Beyond Music; Artistic research